Attributions of emission-reduction and meteorological conditions to typical heavy pollution episodes in a cold metropolis, northeast China - Li, Junfei; Sun, Li; Yao, Xin; Zang, Shuying; Wang, Jiao; Ma, Dalong (Frontiers in Environmental Science, 2023)
Heavy pollution episodes frequently occurred in winter in northeast China due to the multiple anthropogenic emissions coupled with adverse meteorological conditions, which increased the difficulty of environmental pollution control. To better enact strategies for mitigating air pollution in the post-pandemic era, daily pollutant concentration monitoring and meteorological data were used to evaluate the changes and meteorological factors of air pollutants before (2019) and during (2020) the lockdown in Harbin City, northeast China. Moreover, typical pollution episodes under COVID-19 lockdown were identified, and their emission sources, meteorology conditions, and regional pollution transportation were analyzed. The results showed significant decreases in NO2, PM10 and CO, while O3 increased, and no differences in PM2.5 and SO2 during the lockdown compared with non-lockdown periods. It indicated that reduced activities of transportation resulted in reductions of NO2 concentrations by 16%, and stationary emission sources were less affected. Correlation between PM2.5 and O3 tended to change from positive to negative as the threshold of PM2.5 = 90 μg m−3, with the main controlling factor changed from their common gaseous precursors to meteorological conditions (temperature < 0 oC and wind speed < 2 m s−1). Pollution days were concentrated in the COVID-19 lockdown period with PM2.5 as the primary pollutant. SO2 dominant pollution and PM2.5 dominant pollution were distinguished from six sustained heavy pollution events. PM2.5 and SO2 played essential roles in SO2 dominant pollution, which derived from local emissions of coal combustion and firework discharge. PM2.5 dominant pollution might be chemical transformed from coal burning, vehicle exhaust, and other secondary precursors, which was affected and aggravated by CO, NO2, high relative humidity and low wind speed affected by local emission and long-distance transport.